Central Seward Peninsula Deciduous Tall Shrub Map (1950-2018) and Suitable Habitat Model ... - Schore, Aiden; Lara, Mark (NSF Arctic Data Center, 2023)
Tall deciduous shrubs are critically important to carbon and nutrient cycling in high-latitude ecosystems. As Arctic regions warm, shrubs expand heterogeneously across their ranges, including within unburned terrain experiencing isometric gradients of warming. To constrain the effects of widespread shrub expansion in terrestrial and Earth System Models, improved knowledge of local to regional-scale patterns, rates, and controls on decadal shrub expansion is required. Here we map tall deciduous shrub canopies in the central Seward Peninsula of Alaska in 1950 using ~1 meter (m)-resolution aerial photographs from US Navy missions in three subsites (1950ShrubClass.tif and 1950AlderClass.tif) and in 2018 using 3m-resolution PlanetScope satellite imagery for the entire study region (SummerShrubExtent.tif and AlderExtent2017.tif). The timing of alder shrub senescence allowed us to separate the classification into alder and non-alder categories. We computed two change maps: one exclusively for alder and one ...